Effect of The Garlic as Chelation Therapy in Reducing Lead and Cadmium Deposition on Suckling Mice - Bidyut Das; Md. Anwar Hossain; Md. Siddiqul Islam; Md. Aktaruzzaman Zullhash; Md. Mowdudul Hasan Talha; Shahab Uddin Munna; Dwija Sutradhar; Ahasan Ullah Khan (Pandawa Institute, 2024)
The study was conducted on suckling mice to determine the effects of chelation therapy in reducing the deposition of lead (Pb) and cadmium (Cd). A total of 45 suckling mice were randomly divided into three main groups A (control), B, and C. Groups B and C contained Pb and Cd, respectively, at a concentration of 100 mg/kg bwt with 0, 1.70, 3.35, and 6.70% garlic given (B1, B2, B3, B4, and C1, C2, C3, C4). Mice exposed to Pb and Cd exhibited pronounced toxic symptoms along with a marked decrease in total erythrocyte and total leukocyte count, hemoglobin levels, and packed cell volume. Additionally, there is a significant increase in serum glutamate pyruvate transaminase (SGPT) and serum glutamate oxaloacetate transaminase (SGOT) levels. The mean body weight of mice of groups B4, and C4 was the highest among the treated groups. Groups B1 and C1, exposed to Pb and Cd without garlic, showed significant declines in all parameters. Group A (control) shows stable and normal SGOT and SGPT levels. Group C1, exposed to Cd without garlic, experiences the highest increases in both SGOT (98.53 U/L) and SGPT (132.83 U/L), indicating severe liver damage. The group treated with Pb and Cd showed a significant reduction in total erythrocyte count, packed cell volume, and hemoglobin levels after 42-d of treatment. However, mice treated with a combination of Pb, Cd, and 6.70% garlic exhibited nearly normal levels of hematological and biochemical parameters. SGPT and SGOT levels were significantly decreased in all treated groups along with garlic. This experiment demonstrates that garlic possesses both protective and curative effects against Pb and Cd toxicity.